The urban and the rural: Victorian values in John Fowle´s The French Lieutenant´s Women - Berjaková, Eva (Univerzita Pardubice, 2007)
This bachelor paper analyzes the distinctions between the urban and rural Victorian England. It demarcates and characterizes values, moral principles and attitudes that were typical for that period and reflected in all aspects of Victorians’ lives. The paper is based on the novel The French Lieutenant’s Woman by John Fowles and examines to what extent the approach to particular values differed in the countryside and in the cities. The first part of the paper explores the nineteenth-century class system and the mutual relationships in it and presents historical facts about the living conditions in the rural and urban areas. These facts are utilized to analyze how one’s economical situation influenced the observance of the recommended moral principles and conventions. The paper also focuses on the relationship between men and women, their roles in a family, the courtship etiquette and the approach of the nineteenth-century puritan society to sexuality. Further, it provides information on the entertainment and fashion of the Victorians, as these things also varied in different parts of the country.
The urban and the rural: Victorian values in John Fowle´s The French Lieutenant´s Women
Keywords: Victorian age; England; class systems; viktoriánské období; Anglie; třídní systémy